Genomic Characterization of Carbapenemase-Producing Enterobacter hormaechei, Serratia marcescens, Citrobacter freundii, Providencia stuartii, and Morganella morganii Clinical Isolates from Bulgaria - Stefana Sabtcheva; Ivan Stoikov; Ivan N. Ivanov; Deyan Donchev; Magdalena Lesseva; Sylvia Georgieva; Deana Teneva; Elina Dobreva; Iva Christova (MDPI AG, 2024)
Carbapenemase-producing Enterobacter spp. Serratia marcescens, Citrobacter freundii, Providencia spp., and Morganella morganii (CP-ESCPM) are increasingly identified as causative agents of nosocomial infections but are still not under systematic genomic surveillance. In this study, using a combination of whole-genome sequencing and conjugation experiments, we sought to elucidate the genomic characteristics and transferability of resistance genes in clinical CP-ESCPM isolates from Bulgaria. Among the 36 sequenced isolates, NDM-1 (12/36), VIM-4 (11/36), VIM-86 (8/36), and OXA-48 (7/36) carbapenemases were identified; two isolates carried both NDM-1 and VIM-86. The majority of carbapenemase genes were found on self-conjugative plasmids. IncL plasmids were responsible for the spread of OXA-48 among E. hormaechei, C. freundii, and S. marcescens. IncM2 plasmids were generally associated with the spread of NDM-1 in C. freundii and S. marcescens, and also of VIM-4 in C. freundii. IncC plasmids were involved in the spread of the recently described VIM-86 in P. stuartii isolates. IncC plasmids carrying blaNDM-1 and blaVIM-86 were observed too. blaNDM-1 was also detected on IncX3 in S. marcescens and on IncT plasmid in M. morganii. The significant resistance transfer rates we observed highlight the role of the ESCPM group as a reservoir of resistance determinants and stress the need for strengthening infection control measures.